1991
DOI: 10.1002/jor.1100090107
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of a biodegradable composite as an adjunct to internal fixation of proximal femur fractures

Abstract: Internal fixation of comminuted unstable fractures of the severely osteoporotic proximal femur is sometimes supplemented with polymethyl-methacrylate (PMMA). We here report an in vitro biomechanical evaluation of a biodegradable particulate composite that might be used for similar purposes. The composite includes a matrix phase consisting of a hydrolyzable prepolymer [polypropylene fumarate (PPF)] cross-linked with methacrylate monomer, and a particulate phase consisting of tricalcium phosphate and calcium car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Lag screw augmentation in the femoral head (Witschger et al 1991, Choueka et al 1995, Claes et al 1995 and augmentation of intertrochanteric fractures at the fracture site have also been studied (Harrington 1975, Muhr et al 1979, Bartucci et al 1985, Chow et al 1987, Cheng et al 1989). The early results were all reported to be good and few complications from the polymethyl methacrylate cement have occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Lag screw augmentation in the femoral head (Witschger et al 1991, Choueka et al 1995, Claes et al 1995 and augmentation of intertrochanteric fractures at the fracture site have also been studied (Harrington 1975, Muhr et al 1979, Bartucci et al 1985, Chow et al 1987, Cheng et al 1989). The early results were all reported to be good and few complications from the polymethyl methacrylate cement have occurred.…”
Section: Discussionmentioning
confidence: 99%
“…In a mechanical study by Stankewich et al (1996), augmentation with calcium phosphate cement provided enhanced stiffness, stability and strength of fixed femoral neck fractures. When resorbable substances are used, the idea is that the initial reinforcement will be followed by progressive resorption over timeassociated with a simultaneous increase in structural support provided by the healing bone (Witschger et al 1991, Constantz et al 1995, Kopylov et al 1996, Stankewich et al 1996, Mainil et al 1997, Moore et al 1997, Frankenburg et al 1998, Goodman et al 1998, Knaack et al 1998, Yetkinler et al 1999, Larsson and Bauer 2002.…”
mentioning
confidence: 99%
“…This was a consistent finding in both in vitro and in vivo studies and in fractures of the osteoporotic femoral neck and trochanter and was independent of the implants used and the site of application. 48,49,[51][52][53][54][55][56][57][58][59][60][61][62][64][65][66][67][68][69] Eriksson et al 62 confirmed the susceptibility of Norian SRS to shear forces when directly compared with PMMA in the reinforcement of a variety of implants for fixation of the femoral neck. 62 During the pullout test Norian SRS failed through the cement at the periphery of the screw threads whereas PMMA failed at the cement-bone interface.…”
Section: Discussionmentioning
confidence: 90%
“…55,56,60,62 Only one study used a composite. 52 Additionally the study settings differed in terms of the characteristics of the fracture, the implants used, the technique and the location of application of cement (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation